he Impact of Physical Activity during Pregnancy on Weight Gain and Delivery Outcomes - Gimunová, M.; Zvonař, M.; Švancara, J.; Kukla, L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Background: Regular physical activity during pregnancy has been previously associated with preventing delivery complications; however, the current evidence is inconsistent. Therefore, this study analyzes how physical activity affects pre-term birth, Apgar score in the first minute, birth weight, induction of labor, cesarean section, use of analgesia and anesthesia, duration of the second stage of labor and pregnancy weight gain. Methods: The study population, selected from European Longitudinal Study of Pregnancy and Childhood consisted of 2,921 women. Physical activity data were obtained via questionnaires self-administered during the second trimester, while data associated with delivery were obtained via questionnaires administrated by health care professionals. A univariate analysis was used to evaluate the influence of physical activity on delivery complications. The effect of physical activity on weight gain during pregnancy and the second stage of labor duration were tested using a Mann-Whitney test and a one-sample t-test, respectively. Results: Analyzed delivery outcomes were found to be affected by maternal age, pre-pregnancy body mass and the number of previous live births. Neither particular physical activities nor their volume were found to influence delivery complications or the duration of the second stage of labor. However, physical activities such as aerobics, keep fit exercise, swimming, weight training and cycling were found to affect weight gain during pregnancy. Conclusions: Results of this study confirms that current physical activity recommendations for healthy pregnant women are linked to no negative effects on either the delivery or the unborn baby.